Unconventional Hall response in the quantum limit of HfTe5 - Galeski, Stanislaw; Zhao, X.; Wawrzynczak, Rafal; Meng, Tobias P; Forster, T.; Lozano, P. M.; Honnali, S.; Lamba, N.; Ehmcke, Toni; Markou, Anastasios; Li, Q.; Gu, G.; et al. (Nature Communications, 2020)
Interacting electrons confined to their lowest Landau level in a high magnetic field can form a variety of correlated states, some of which manifest themselves in a Hall effect. Although such states have been predicted to occur in three-dimensional semimetals, a corresponding Hall response has not yet been experimentally observed. Here, we report the observation of an unconventional Hall response in the quantum limit of the bulk semimetal HfTe5, adjacent to the three-dimensional quantum Hall effect of a single electron band at low magnetic fields. The additional plateau-like feature in the Hall conductivity of the lowest Landau level is accompanied by a Shubnikov-de Haas minimum in the longitudinal electrical resistivity and its magnitude relates as 3/5 to the height of the last plateau of the three-dimensional quantum Hall effect. Our findings are consistent with strong electron-electron interactions, stabilizing an unconventional variant of the Hall effect in a three-dimensional material in the quantum limit.
CRIS-Team Scopus Importer:2022-04-14